Management of the First Stage of Labor with Electronic Vibration: Manajemen Persalinan Kala I dengan Vibrasi Elektronik - Yanik Purwanti; Arief Wisaksono (Universitas Muhammadiyah Sidoarjo, 2022)
Prolonged labor is potentially dangerous for the mother and fetus. This can be prevented by stimulating the release of the hormone oxytocin to increase uterine contractions so that prolonged labor does not occur. So a tool is needed to stimulate the hormone oxytocin which is made as comfortable as possible. Apart from helping speed up the process of the first stage of labor, this tool can also stimulate the release of the hormone prolactin to help milk production. This system was designed using the Arduino Uno microcontroller type ESP8266, working to stimulate the nipples through vibration. From the results of this study it was found that the vibrations produced could help stimulate the release of the hormone oxytocin so that the first stage of labor took place 72.40% faster than the old theory of the first stage of labour. Highlights: Prolonged labor risks: Emphasizes the potential danger for both mother and fetus in cases of prolonged labor. Oxytocin stimulation: Highlights the importance of stimulating oxytocin release to prevent prolonged labor and promote uterine contractions. Arduino Uno and nipple vibration: Introduces the specific tool designed using Arduino Uno microcontroller and nipple vibration for oxytocin stimulation during labor. Keywords: prolonged labor, oxytocin stimulation, Arduino Uno, nipple vibration, faster labor